Acolhimento na percepção dos enfermeiros da Atenção Primária à Saúde - da Silva Marques-Ferreira, Maria de Lourdes; do Vale Barreira-Penques, Rosana Maria; Sanches-Marin, Maria José (Universidad de la Sabana, 2014)
Objective: This paper is intended to explore how nurses working in primary health care perceive acceptance. Method: It is based on a qualitative study conducted through interviews with 21 nurses from eight municipalities in the State of São Paulo. A phenomenological approach was used in data analysis. Results: It was found that nurses' understanding of acceptance, at certain points in time, comes close to the principles and guidelines of the Unified Health System (SUS). Conclusions: Nursing professionals manifest difficulties with the structure, organization and management of health services and express actions and beliefs related to the traditional model of care. The various stakeholders need to join forces if acceptance is to be achieved.
Acceptance in the perception of nurses involved in primary health care
Keywords: Health system; Male; Nurses; Nursing; Primary health care; User embracement